ANALISIS IMPLEMENTASI PROJECT BASED LEARNING (PJBL) DENGAN PENDEKATAN DEEP LEARNING TERHADAP KONSENTRASI BELAJAR SISWA SEKOLAH DASAR - Ahsin Takiyudin Haniah; Fajar Sri Utami; Harun Joko Prayitno; Dhany Efita Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of implementing Project-Based Learning (PjBL) with a deep learning approach on the concentration of elementary school students. The study employed a quantitative approach using a quasi-experimental design of the pretest-posttest control group type. The research sample consisted of 60 fourth-grade elementary school students divided into an experimental group and a control group each consisting of 30 students. The experimental group received instruction using a Project-Based Learning model grounded in deep learning, while the control group followed conventional instruction. Data were collected using a learning concentration questionnaire that met validity and reliability criteria (Cronbach’s Alpha = 0.856). Data analysis was conducted using the Shapiro-Wilk normality test, Levene’s test of homogeneity, and hypothesis testing via the independent samples t-test. The results of the study indicate that the data are normally distributed and homogeneous. The mean score for the experimental group was 59.47, while that for the control group was 58.93. The results of the hypothesis test showed a significance value of 0.769 (p > 0.05), indicating no significant difference between the two groups. Thus, the implementation of Project-Based Learning using a deep learning approach has not yet had a significant impact on the concentration of elementary school students. Nevertheless, the experimental group showed a slightly higher average score compared to the control group, suggesting that this model has the potential to support increased student engagement in learning. Further research is recommended to implement interventions over a longer period and involve a larger sample size in order to obtain a more comprehensive understanding of the effectiveness of deep learning-based project-based learning on students' concentration.